Pest insect management in vegetable crops grown outdoors in northern Europe – approaches at the bottom of the IPM pyramid - Collier, Rosemary (Frontiers in Horticulture, 2023)
Vegetables are a key component of a healthy diet, but they are also exposed to a relatively high amount of pesticide usage in conventional growing systems. The generally agreed aim of Integrated Pest Management (IPM) is to reduce reliance on ‘chemical control’ using synthetic pesticides, usually placed at the top of the IPM pyramid. This review focuses on the approaches at the bottom of the IPM pyramid in relation to the pest insects of root, bulb and leafy vegetable crops in northern Europe. These concern establishment of the crop before any additional treatments are applied; summarised as 1) what to plant (crop and cultivar(s)), 2) where to plant it (considering a range of spatial scales) and 3) what to plant it with (companion species, wildflowers etc.). Were it possible to identify sources of resistance or partial resistance to all key pests and pathogens of vegetables and breed these into commercial cultivars, this would undoubtedly be an effective and ‘reliable’ way forward. Increased use of rotation and the isolation of ‘new’ crops from sources of infestation could also be a reliable approach to the management of certain pests, especially those with a limited capacity to disperse. For some growers, there would be a need to alter the ‘spatial arrangement’ of their cropping system to maximise the benefits and this might involve more cooperation with neighbours. Finally, although there appears to be much potential, the benefits of increasing the diversity of plant species within and around crops are currently hard to quantify with regard to pest management and thus might be considered to be less ‘reliable’ approaches at present. It is vital, therefore, that there is a greater understanding of the mechanisms involved and of how it may be possible to achieve a more consistent effect from the range of approaches available.